Pacte ethnographique et film documentaire - Jean-Pierre Olivier de Sardan (Images du Travail, Travail des Images)
What are the relationships between visual anthropology (« ethnographic cinema ») and documentaries ? The author, showing the opposition between these two forms is essentially a false problem, examines the ethical and technical dimensions of the realist pact and its variant, the ethnographic pact, and gives a detailed description of the complex system of choices, common to all kinds of documentaries, through which the ethngraphicity of a documentary film manifests itself.